Metabolic positron-emission tomography/magnetic resonance imaging in primary progressive aphasia and frontotemporal lobar degeneration subtypes: Reassessment of expected [18F]-fluorodeoxyglucose uptake patterns - Franceschi, Ana M.; Naser-Tavakolian, Kiyon; Clifton, Michael; Bangiyev, Lev; Cruciata, Giuseppe; Clouston, Sean; Franceschi, Dinko (World Journal of Nuclear Medicine, 2021)
Clinical assessment of frontotemporal lobar degeneration (FTLD)/primary progressive aphasia (PPA) patients is challenging, given that common cognitive assessments rely extensively on language. Since asymmetry in neuroimaging biomarkers is often described as a central finding in these patients, our study evaluated [18F]-fluorodeoxyglucose (FDG) uptake patterns in patients meeting clinical and imaging criteria for FTLD, with emphasis on PPA. Fifty-one subjects underwent brain [18F]-FDG positron-emission tomography/magnetic resonance imaging (PET/MRI) as part of their routine clinical workup for dementia and neurodegenerative disease. Images were obtained using a Siemens Biograph mMR integrated 3T PET/MRI scanner. PET surface maps and fusion fluid-attenuated inversion recovery-PET images were generated utilizing MIMneuro software. Two board-certified neuroradiologists and one nuclear medicine physician blinded to patient history classified each FTLD/PPA subtype and assessed for left- versus right-side dominant hypometabolism. Qualitative and semiquantitative assessment demonstrated 18 cases of PPA, 16 behavioral variant frontotemporal dementia (bvFTD), 12 corticobasal degeneration, and 5 progressive supranuclear palsy. Among the 18 PPA subjects (11 svPPA, 5 lvPPA, and 2 agPPA), 12 (67%) demonstrated left-dominant hypometabolism and 6 (33%) right-dominant hypometabolism. While existing literature stresses left-dominant hypometabolism as a key imaging feature in the PPA subtypes, a third of our cases demonstrated right-dominant hypometabolism, suggesting that emphasis should be placed on the functionality of specific brain regions affected, rather than left versus right sidedness of hypometabolism patterns.
Keywords: [18F]-fluorodeoxyglucose; frontotemporal lobar degeneration; hybrid neuroimaging; positron emission tomography/magnetic resonance imaging; primary progressive aphasia